Evaluation of antibody titers, specific hematological parameters, and clinical manifestations correlated of SARS-CoV-2 infection Among symptomatic COVID-19 patients at the Brak isolation center in Libya. (Comprehensive Journal of Science, 2025)
Coronaviruses are a group of viruses that make mammals and birds sick. Some members of this group can infect people, and the new coronavirus (SARS-CoV-2) is a new strain of this group. It is the cause of the current worldwide pandemic, and it has never been found in people before. The virus can be passed from animals to people. This study was conducted to investigate the disease's distribution among patients and to evaluate antibody titers, considering the limited research on this virus in Libya despite its prevalent occurrence in various regions. Results: An analysis of 25 confirmed cases showed that men (18 cases; 72%) were more likely to get infected than women (7 cases; 28%).The results showed that the risk of getting an infection went up with age, especially for people between the ages of 50 and 59. The most common clinical sign was fever, which was present in 23 cases (92%). Additionally, individuals with chronic conditions, including diabetes mellitus and hypertension, exhibited a heightened susceptibility to infection (41.9%). Pearson's correlation analysis indicated a positive association between CRP and D-dimer (R = 0.5, P = 0.06), although it lacked statistical significance. The lymphocyte count showed a negative correlation with CRP (R = -0.5, P = 0.3) and D-dimer (R = -0.5, P = 0.1), but neither of these correlations was statistically significant.
Keywords: SARS-COV-2, COVID-19, Antibody titers, Clinical manifestations , Hematological parameters